SHALAT MEMAKAI MASKER DITINJAU DARI PERSPEKTIF MAQASID SYARI’AH - Nasution, Mulkan (IAIN Padangsidimpuan, 2021)
This paper describes how the benefits and benefits of masks when worn when performing prayers. To find this answer, the author uses a qualitative method, specifically a literature study by tracing the opinions of scholars who discuss the topic of this paper and then concludes.The finding in this article is that praying using a three-layer mask or in accordance with the recommendation from the Ministry of Health of the Republic of Indonesia, has many benefits, including self-preservation or in the term of fiqh proposal, namely hifznafs (self-preservation) including from the threat of transmission of the Covid virus - 19.